Scoping review of the association between bacterial vaginosis and emotional, sexual and social health - Judith Brusselmans; An De Sutter; Brecht Devleesschauwer; Hans Verstraelen; Piet Cools (BMC, 2023)
Abstract Background Bacterial vaginosis (BV) is a condition that, if symptomatic, is characterized by discharge and odor, with high recurrence rates even when treated. This study aims to review what literature exists on the association between BV and the emotional, sexual, and social health of women. Methods MEDLINE, Embase and Web of Science databases were searched from inception until November 2020. Studies reporting an association between women's emotional, sexual and/or social health and symptomatic BV in a qualitative and/or quantitative manner were included. Selected studies were divided in three categories, i.e. reporting on the emotional, sexual and/or social association. All studies were critically evaluated and discussed. Results Sixteen studies were included. Concerning emotional health, we found eight studies that calculated the association between stress and BV, in four this was statistically significant. Four qualitative studies on emotional health showed that the severity of the symptoms influenced the impact on women's lives. All studies on sexual health reported that many women experienced an impact on their relationship and sexual intimacy. Results for social life ranged from no association found to most of the study population showing avoidance behavior. Conclusion This review shows that symptomatic BV can be associated with diminished emotional, sexual, and social health, but there is too little evidence to state the extent of this association.